Are non-competitors greener? The effect of consumer awareness differences on green food consumption - Zheng, Manhua; Zheng, Qiujin; Chen, Jianhong; Tang, Decong (Frontiers in Psychology, 2023)
Green consumption plays a crucial role in mitigating environmental degradation. Governments and corporations are actively fostering the growth of green consumption. The escalating environmental issues have awakened consumers' environmental and competitive awareness, which significantly aids in increasing the probability of green food consumption. This research, grounded in the Self-Consistency Theory and the Theory of Planned Behavior, constructs a model to examine the impact of consumer competitive awareness and environmental awareness on green food purchase intentions. Based on data from 700 consumer surveys analyzed through structural equation modeling, the study reveals that consumer competitive awareness negatively influences green self-efficacy and perceived control. In contrast, environmental awareness positively impacts green self-efficacy and perceived control. Both green self-efficacy and perceived control positively affect the green food purchase intention. Notably, the negative impact of competitive awareness on perceived control is greater than its impact on green self-efficacy, while the positive influence of environmental awareness on green self-efficacy outweighs its impact on perceived control. The positive effect of green self-efficacy on green food purchase intention surpasses that of perceived control. Therefore, enhancing media publicity, and educational initiatives, improving purchasing convenience and comfort, establishing communication forums and green food recognition mechanisms, conducting experiential activities, showcasing consumption guides, and setting role models can elevate consumer purchase intentions. This study contributes to enhancing the understanding of consumer psychology in green food consumption for governments and businesses, offering valuable insights for marketing green food products.